Eye of Europe Foresight Training Manual - Knudsen, Mikkel; Kaskinen, Juha; Lauttamäki, Ville (My University, 2026)
The following document outlines the Eye of Europe Foresight Training Manual. The manual is developed by the Finland Futures Research Centre (FFRC), University of Turku, as part of the Work Package 4 (Futures Literacy) of the Eye of Europe project.
The deliverable is submitted at month 10 of project (August 2024) after the delivery of prior pilot training for foresight beneficiaries. The purpose of the manual is to define and establish foresight training target groups, to describe, on a high level, intended training inputs and outcomes, and to document and reflect upon the first practical training activities of the project.